(3GdeNJUQ GdcHjQ aj Gdabg GdeGdcis - (3YHO Gddg Hf GdMce Hf GYjf GdeUQj, CHh eMeO,J (B214 (3g` s
(3ChdgG (B:s
(3cJGH GdML ef eNJUQ YHO Gddg Hf YHO GdMcje GdcHjQ eG LGA ai GdML MOKfG CHh GdYHGS CMeO Hf GHQGgje bdJ CQCjJ ef CQGO Cf jgd HGdML CjZJSd s
(3BNQgG (B:s
(3hSFd eGdc Yf GdQLd jbOe ef SaQ aJdbGg EHfJg Ch CNJg aJbHdg abGd dG HCS HPdc abjd dg CaJQi Cf JbHdg NJfJg abGd dGJbjdg NJfI dG HCS HPdc abjd dg CaJQi Cf JbHdg NJfJg abGd dGJbHdg NJfI s
(3GdfSNI HgG MhGTs
(3bWYI efgs
(3fSNI Ydi Qb ZRGd s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI eHJhQI GdBNQ , HgG NQe s
Keywords: (3Gdabg GdeGdcjs